Mutations Affecting DNA-Binding Activity of the MexR Repressor of mexR-mexA-mexB-oprM Operon Expression - Saito, Kohjiro (American Society for Microbiology, 2003)
We have isolated 25 MexR mutants that retained their dimerizing ability but were unable to bind mexOP DNA. Surprisingly, 20 mutations were located in the hydrophobic core region at α4, W1, α2, α3, and β2, and only 3 were in positively charged residues. These results verified that DNA binding is mediated by distinct regions of MexR and showed the importance of the hydrophobic core region of the DNA-binding domain.